Optical coherence tomography as a method to identify parathyroid glands. Issue 10 (19th November 2013) - Ladurner, Roland; Hallfeldt, Klaus K.J.; Al Arabi, Norah; Stepp, Herbert; Mueller, Susanna; Gallwas, Julia K.S.
Abstract Background and Objective The identification of parathyroid glands can be a major problem in parathyroid surgery. The purpose of this study was to evaluate the feasibility of optical coherence tomography (OCT) in distinguishing between parathyroid tissue, thyroid tissue, lymph nodes, and adipose tissue. Methods Ex vivo OCT images as well as histological sections were generated from parathyroid glands, thyroid tissue, lymph nodes and fat in order to define significant morphologic differences between these entities. As a second step all OCT images were separately evaluated by two blinded investigators and later compared to the corresponding histology. Sensitivity and specificity of OCT in distinguishing between the different tissues were determined. To assess the interobserver agreement, κ coefficients were calculated from the ratings of each investigator for each OCT image seen. Results A total of 320 OCT images from 32 patients undergoing thyroid surgery, parathyroidectomy or lymphadenectomy were compared with the corresponding histology. The sensitivity and specificity in distinguishing parathyroid tissue from the other entities was 84% (second investigator: 82%) and 94% (93%) respectively. Unweighted κ using four diagnostic categories was 0.97 (95% CI, 0.94–0.99) showing substantial agreement between both investigators. Conclusion OCT is highly sensitive in distinguishing between parathyroid tissue, thyroid tissue, lymph nodes and adipose tissue. These ex vivo results should be confirmed by using OCT imaging intraoperatively. Lasers Surg. Med. 45:654–659, 2013. © 2013 Wiley Periodicals, Inc.